2014 36th Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2014
DOI: 10.1109/embc.2014.6944647
|View full text |Cite
|
Sign up to set email alerts
|

Changes in music tempo entrain movement related brain activity

Abstract: The neural mechanisms of music listening and appreciation are not yet completely understood. Based on the apparent relationship between the beats per minute (tempo) of music and the desire to move (for example feet tapping) induced while listening to that music it is hypothesised that musical tempo may evoke movement related activity in the brain. Participants are instructed to listen, without moving, to a large range of musical pieces spanning a range of styles and tempos during an electroencephalogram (EEG) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 22 publications
1
18
0
Order By: Relevance
“…Our findings reveal a relationship between motor and auditory cortices in all frequency ranges studied, but most prominent in the α (8–12 Hz) and β (12.5–18 Hz) ranges. These findings are consistent with prior reports in the literature (e.g., Janata and Grafton, 2003 ; Bauer et al, 2014 ; Daly et al, 2014a ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings reveal a relationship between motor and auditory cortices in all frequency ranges studied, but most prominent in the α (8–12 Hz) and β (12.5–18 Hz) ranges. These findings are consistent with prior reports in the literature (e.g., Janata and Grafton, 2003 ; Bauer et al, 2014 ; Daly et al, 2014a ).…”
Section: Discussionsupporting
confidence: 93%
“…Activity in the α range (8–13 Hz) was also found to be associated with tempo modulations. Daly et al ( 2014a ) report strong α range event-related desynchronization over the left motor cortex, correlated with the variation in musical tempo. In a related study, Yuan et al ( 2009 ) looked at changes in EEG spectral power when listening to tempo-transformed music.…”
Section: Introductionmentioning
confidence: 99%
“…Up-regulation of high-frequency waves in the frontal and frontal-central areas could 327 be associated with the psychological benefits that are commonly induced by music during 328 activities of daily life such as walking (Daly, Hallowell, et al, 2014;Daly, Malik, et al, 329 2014). Previous experiments have indicated that environmental sensory cues have the 330 potential not only to up-regulate high-frequency components of the power spectrum, but also 331 to downregulate theta waves in the frontal regions (Bigliassi et al, 2016b).…”
Section: Frequency Of Cortical Rhythms 326mentioning
confidence: 99%
“…Tapping along with music rhythms induces beat-related entrainment (Nozaradan et al, 2015) as well as changes in functional somatosensory networks (Daly et al, 2014) and behavior (Nozaradan et al, 2016;Crasta et al, 2018). Importantly, rhythm entrainment is not limited to the auditory modality (Okawa et al, 2017) and can occur in the absence of an external stimulus.…”
Section: Entrainment Of Neural Oscillationsmentioning
confidence: 99%